Optimal Dose of Serotonin Reuptake Inhibitors for Obsessive-Compulsive Disorder in Adults: A Systematic Review and Dose–Response Meta-Analysis - Xu, Jiao; Hao, Qinjian; Qian, Ruiyi; Mu, Xingyu; Dai, Minhan; Wu, Yulu; Tang, Yiguo; Xie, Min; Wang, Qiang (Frontiers in Psychiatry, 2021)
Background: Obsessive compulsive disorder (OCD) is a common chronic mental disorder with high disability rate. Serotonin re-uptake inhibitors (SRIs), including selective serotonin re-uptake inhibitors (SSRIs) and tricyclic antidepressants, such as clomipramine, are the most choices for pharmacological treatment of OCD. Optimizing their use is pivotal in guiding clinical practice of OCD; however, there are few studies on the optimal dose of SRIs and controversy about their dose-response relationship or optimal target dose are underway. Therefore, the objectives of this study were to summarize the existing evidence to determine whether there is a relationship between the dose and effect of SRIs, as well as the optimal dose of SRIs for OCD, and to propose future research directions. Methods: Medline, Embase, Biosis, PsycINFO, Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science and CINAHL were searched for relevant publications and the search was up to Feb 22, 2020. We used a one-stage, robust error meta-regression (REMR) model to dealing with the correlated dose-response data for SRIs from different studies. Doses of SRIs were converted to fluoxetine equivalents when doing dose response analysis. Review Manager Program Version 5.3 and STATA software package (version 15.1) were applied to analyze data. The study protocol was registered with PROSPERO, number CRD42020168344. Results: Eleven studies involving 2322 participants were included in final analysis. For SRIs, the dose-efficacy curve showed a gradual increase trend in the 0-40 mg doses range, and then had a decreased trend in doses range up to 100 mg fluoxetine equivalent. Dropouts due to adverse effects gradually increased throughout the inspected dose scope. The curve of dose all-cause dropouts showed that there was no relationship between them. Sensitivity analysis showed that these results were robust. Conclusion: The systematic review found that the optimal dose of efficacy was about 40 mg fluoxetine equivalent. Tolerability decreased in the licensed doses and there was no significant correlation between acceptability and doses of SRIs. Therefore, the optimal dose of SRIs needed to consider both the effectiveness and tolerability factors.